L’école maternelle au service des besoins fondamentaux de l’enfant : résultats d’une expérimentation sur les besoins de sécurisation et d’exploration - Hélène Marquié-Dubié (Éducation et Socialisation)
Nursery school serving the fundamental needs of the child: an experiment on the needs for security and exploration. In this article are presented the first results obtained within the framework of an experiment of innovative class device for the nursery school (Experimental Project of Training of the Teachers of Kindergarten). These are organized stays in a place allowing free movement of students between the different spaces set up to allow independent activities, including outside. In this context, adults (teachers and other caregivers) are asked to intervene as little as possible on the students' activity and to support them in carrying out the projects they freely choose. The question of feelings of security and attachment (Bolwby, 1969) of the children identified by the teachers as having specific needs is the first element on which our reflection focused and was the starting point for action research (Morrissette, 2013) conducted. The results of the study carried out on this subject show that the device has a positive impact on the most disadvantaged children.